Evaluating the efficacy of a web-based self-help intervention with and without chat counseling in reducing the cocaine use of problematic cocaine users: the study protocol of a pragmatic three-arm randomized controlled trial. Issue 1 (December 2015) - Schaub, Michael; Maier, Larissa; Wenger, Andreas; Stark, Lars; Berg, Oliver; Beck, Thilo; Quednow, Boris; Haug, Severin
Abstract Background Web-based self-help interventions that aim to reduce problematic substance use are able to reach "hidden" consumer groups in the general population who often fear stigmatization and thus avoid institutional addiction treatment. In Western European countries, including Switzerland, cocaine is the most widely used psychoactive substance after alcohol, tobacco, and cannabis. Although approximately one in six users develop serious problems of dependency, only a minority seeks help from psychiatrists or in outpatient counseling centers or psychiatric hospitals. Offering web-based therapy treatment may potentially reach users who hesitate to approach institutional treatment services and help them reduce their cocaine use before they get into more serious trouble. Methods/design The study will use a three-arm randomized controlled trial (RCT) design to test the efficacy of a web-based self-help intervention with or without guided chat counseling compared with that of a waiting list control condition in reducing or stopping cocaine use. The primary outcome measure will be the weekly quantity of cocaine used. Secondary outcome measures will include the number of cocaine use days in the past 30 days, the severity of cocaine dependence, the use of alcohol, tobacco, and/or other illicit drugs, changes in mental health symptoms, and treatment retention. The self-help intervention will consist of eight modules that are designed to reduce cocaine use and depression symptoms. These modules are based on the principles of Motivational Enhancement Therapy and Cognitive Behavioral Therapy, such as Behavioral Self-Management. The three individual chat therapy sessions will be based on the same therapy approaches and will be tailored to participants' self-help data and aim to assist the reinstatement of social rewards and the improvement of social support and relationships. Discussion This study will be the first RCT to test the effectiveness of a web-based self-help intervention in combination with or without chat counseling in reducing cocaine use. The expected findings will contribute substantial knowledge that may help design effective guided and unguided web-based treatment for cocaine users. Moreover, the study will elucidate to what extent a therapeutic alliance with cocaine users can be established in a guided Internet-delivered setting. Additionally, the present study will investigate changes in social support with specific guided therapy interventions that aim to ameliorate social support and social perceptions and compare these changes with those in an unguided self-help intervention Trial Registration Current Controlled TrialsISRCTN12205466 . Registered 24 February 2015.